Workforce development in community pharmacies in England: Opportunities and tensions for a private sector provider of NHS services. - Jayne L Astbury; Sally Jacobs; Imelda McDermott; Sarah C Willis; Aidan Moss; Selma Stearns; Catherine Fenton; Ali M K Hindi; Elizabeth M Seston; Ellen I Schafheutle (PLoS ONE)
Background The intention to more effectively mobilise and integrate the capabilities of the community pharmacy workforce within primary care is clearly stated within National Health Service (NHS) England policy. The Pharmacy Integration Fund (PhIF) was established in 2016 to support the development of clinical pharmacy practice in a range of primary care settings, including community pharmacy. Objective This study sought to determine how PhIF funded learning pathways for post-registration pharmacists and accuracy checking pharmacy technicians enabled community pharmacy workforce transformation, in what circumstances, and why. Methods Realist evaluation. We identified two main programme theories underpinning the PhIF programme and tested these theories against data collected through 41 semi-structured qualitative interviews with community pharmacist and pharmacy technician learners, educational supervisors, and community pharmacy employers. Results The data supported the initial programme theories and indicated that the learning pathway for post-registration pharmacists had also provided opportunity for pharmacists to develop and consolidate their clinical skills before pursuing an independent prescribing qualification. Employer support was a key factor influencing learner participation, whilst employer engagement was mediated by perceptions of value expectancy and clarity of purpose. The study also highlights the influence of contextual factors within the community pharmacy setting on opportunities for the application of learning in practice. Conclusions When designing and implementing workforce transformation plans and funded service opportunities that require the engagement of a diverse range of private, for-profit businesses within a mixed economy setting, policymakers should consider the contextual factors and mechanisms influencing participation of all stakeholder groups.